Consumption effects of genetic modification: what if consumers are right? - Giannakas, Konstantinos; Fulton, Murray (International Food Policy Research Institute, 2000)
This paper develops a model of differentiated consumers to examine the consumption effects of genetic modification (GM) under alternative labeling regimes and segregation enforcement scenarios. Analytical results show that if consumers perceive GM products as being different than their traditional counterparts, genetic modification affects consumer welfare and, thus, consumption decisions. When the existence of market imperfections in one or more stages of the supply chain prevents the transmission of cost savings associated with the new technology to consumers, genetic modification results in welfare losses for consumers. The analysis shows that the relative welfare ranking of the “no labeling” and “mandatory labeling” regimes depends on: (i) the level of consumer aversion to genetic modification, (ii) the size of marketing and segregation costs under mandatory labeling; (iii) the share of the GM product to total production; and (iv) the extent to which GM products are incorrectly labeled as non-GM products.